Antenatal corticosteroids and neonatal outcomes according to gestational age: a cohort study. Issue 2 (29th November 2009) - Manktelow, Bradley N; Lal, Mithilesh K; Field, David J; Sinha, Sunil K
Abstract : Objective: To see whether there was any difference in the effect of antenatal corticosteroids on neonatal outcomes according to different gestational ages at birth. Methods: This was a prospective cohort study in a geographically defined population (Trent region, UK). All infants admitted for neonatal care, of 23–32 weeks' gestation, born to Trent resident mothers over the 15-year period between 1993 and 2007 were included. Antenatal corticosteroid treatment was given to pregnant women at risk of preterm birth. The primary outcome was survival until discharge from neonatal unit. Secondary outcomes included length of stay on the neonatal unit, duration of artificial respiratory support (mechanical ventilation and continuous positive airway pressure (CPAP)) and chronic lung disease (CLD). Results: The overall mortality among babies born between 24 and 29 weeks with maternal steroids was lower (n=850 out of 4370; 19.4%) as compared to their counterparts whose mothers did not receive steroids (n=323 out of 920; 35.1%) The gestation-specific mortality figures (%) in the steroid treated group between 24 and 29 weeks' gestation were 61.5, 36.9, 28.5, 17.5, 10.2 and 5.1, respectively, and this was significantly lower than the group without steroid treatment. There was a 9.9% reduction in mortality among babies born at 23 weeks' gestation in the steroid treated group (n=81 out of 102; 79.4%) compared to the non-steroid group (n=75 out of 84; 89.3%), but this did not reach statistical significance (p=0.068). There was no significant effect of antenatal steroid treatment on length of stay, duration of respiratory support and CLD among infants who survived until discharge. There was no trend in survival in the two groups over the 15-year study period. Conclusions: Antenatal corticosteroid treatment is associated with improved survival in babies born between 24 and 29 weeks' gestation. This, however, does not lead to any significant improvements in length of stay, duration of respiratory support and CLD among survivors.